Extracellular Vesicles Secreted in Response to Cytokine Exposure Increase Mitochondrial Oxygen Consumption in Recipient Cells - Russell, Ashley E.; Jun, Sujung; Sarkar, Saumyendra; Geldenhuys, Werner J.; Lewis, Sara E.; Rellick, Stephanie L.; Simpkins, James W. (Frontiers in Cellular Neuroscience, 2019)
Extracellular vesicles (EVs) are small, membrane-bound nanoparticles released from most, if not all cells, and can carry functionally active cargo (proteins, nucleic acids) which can be taken up by neighboring cells and mediate physiologically relevant effects. In this capacity, EVs are being regarded as novel cell-to-cell communicators, which may play important roles in the progression of neurodegenerative diseases, like Alzheimer’s disease. Aside from the canonical physical hallmarks of this disease (amyloid β plaques, neurofibrillary tangles, and widespread cell death), AD is characterized by chronic neuroinflammation and mitochondrial dysfunction. In the current study, we sought to better understand the role of tumor necrosis factor-alpha (TNF-α), known to be involved in inflammation, in mediating alterations in mitochondrial function and EV secretion. Using an immortalized hippocampal cell line, we observed significant reductions in several parameters of mitochondrial oxygen consumption after a 24-hour exposure period to TNF-α. In addition, after TNF-α exposure we also observed significant upregulation of two miRNAs (miR-34a and miR-146a) associated with mitochondrial dysfunction in secreted EVs. Despite this, when naïve cells are exposed to EVs isolated from TNF-α treated cells, mitochondrial respiration, proton leak, and reactive oxygen species (ROS) production are all significantly increased. Collectively these data indicate that a potent proinflammatory cytokine, TNF-α, induces significant mitochondrial dysfunction in a neuronal cell type, in part via the secretion of EVs, which significantly alter mitochondrial activity in recipient cells.